CONCEPTUAL FOUNDATIONS OF THE ELECTRONIC PLATFORM OF EXPERTISE - Nurbekova, Ж.К.; Sagimbaeva, А.Е.; Baigusheva, К.М.; Naimanova, Д.С.; Dosymbek, Д.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Currently, one of the urgent problems is the creation of an electronic platform for the examination of textbooks. Currently, the preparation of textbooks for schools and universities and their examination, guided by the criteria of examination, is a rather complex process. The purpose of the article is to develop the conceptual foundations of the electronic platform for the examination of textbooks. The study uses methods of analysis of regulatory documents, questionnaires on the problem posed. The purpose of the questionnaire is to collect expert opinions on the experience and knowledge of the examination of the content of education and educational resources for the collective strengthening and improvement of the examination process. The results of the study. With the introduction of the stages of organizing and conducting the examination of educational publications and standard curricula, programs, the purpose and content of the electronic platform for the examination of educational content and educational resources (EPEC), the architecture of the EPEC electronic platform-the external contour (functional Web portal), the internal contour (BI-analytics, intelligent block, Blockchain module, monitoring systems processes and logging of user actions, query processing systems), data exchange systems, DBMS. The stages of creating an electronic platform are given, taking into account the technical features of the electronic platform.